2008
DOI: 10.1016/j.nimb.2008.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Studies of uranium carbide targets of a high density

Abstract: Production of Cs and Fr isotopes from uranium carbide targets of a high density has been investigated at IRIS (Investigation Radioactive Isotopes at Synchrocyclotron), Gatchina. The UC target material with a density of 12 g/cm3 was prepared in a form of pellets. Two targets were tested on-line under the same temperature conditions: (a) a reference small target with a thickness of 4.5 g/cm2; (b) a heavier (so called intermediate) target with a thickness of 91 g/cm2. Yields and release efficiencies of nuclides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Making use of beams of different bombarding particles -protons, neutrons, and heavy ions, the ISOL installations at present provide the production of considerably more than 2000 mass-separated isotopes of almost all elements of the periodic system. The on-line mass-separator facilities like ISOLDE (CERN, Switzerland) [6], ISAC (Isotope Separation and ACceleration, TRIUMF, Canada) [7], IRIS (Investigations of Radioactive Isotopes on Synchrocyclotron, PNPI, Gatchina) [8] and many others enabled the production of radioactive isotopes with half-lives from several milliseconds to several thousand years which are used for studying in nuclear physics, solid-state physics, and for some medical physics experiments. The first experiments on receiving mass-separated medical radionuclides for tests on animals [9,10] were made at the ISOLDE installation which is used in general for nuclear physics research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Making use of beams of different bombarding particles -protons, neutrons, and heavy ions, the ISOL installations at present provide the production of considerably more than 2000 mass-separated isotopes of almost all elements of the periodic system. The on-line mass-separator facilities like ISOLDE (CERN, Switzerland) [6], ISAC (Isotope Separation and ACceleration, TRIUMF, Canada) [7], IRIS (Investigations of Radioactive Isotopes on Synchrocyclotron, PNPI, Gatchina) [8] and many others enabled the production of radioactive isotopes with half-lives from several milliseconds to several thousand years which are used for studying in nuclear physics, solid-state physics, and for some medical physics experiments. The first experiments on receiving mass-separated medical radionuclides for tests on animals [9,10] were made at the ISOLDE installation which is used in general for nuclear physics research.…”
Section: Methodsmentioning
confidence: 99%
“…A high-temperature method of extraction of 223,224 Ra produced by protons in 238 UC was described in detail in [11]. In our experiments, we used the UC target (uranium-238 mono carbide of a high density [8,11]) for production and a high-temperature extraction of radium isotopes. It was demonstrated that investigated target materials can be used as well for the massseparator target construction of the mass-separator station for production at RIC-80 radioisotope medical beams of very high purity.…”
mentioning
confidence: 99%
“…The mass-separated isotopes 223,224 Ra and 225 Аc were produced at the ISOL facility IRIS (Investigation of Radioactive Isotopes at Synchrocyclotron) [9] working on-line with a 1-GeV proton beam of the synchrocyclotron of Petersburg Nuclear Physics Institute (Gatchina, Russia). 223,224 Ra and 225 Аc were produced in a UC target, ionized in a high-temperature surface ionization source, were extracted and accelerated by a 30 kV potential difference.…”
Section: On-line Production Of Mass-separated Isotopes 223224 Ra and 225 Ac At The Iris Massseparatormentioning
confidence: 99%
“…The main problem -the extraction and isotopic separation produced radio nuclides is under successful solution for almost 50 years already by means of ISOL installations at beams of different bombarding particles -protons, neutrons and heavy ions. Such on-line systems like ISOLDE (CERN, Switzerland), ISAC (TRIUMF, Canada), IRIS (PNPI, Gatchina) [2,3,4] operation on-line at proton beams, allows to obtain at present more than 2000 separated isotopes of almost all elements of the Periodic system. Produced radioactive isotopes with half-life from several milliseconds to several thousand years are used in nuclear physics study, in study of solid state physics and in the radiation medicine.…”
Section: On-line Mass-separator At Ric-80 Installation To Obtain Medimentioning
confidence: 99%